Kidney donation: bridging the gap in the shortage of kidney transplants in Malaysia - Farida Islahudin; Intan Azura Shahdan; Li Ming Kua (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this study was to identify factors that affect willingness to donate kidneys posthumously among Malaysians. Design/methodology/approach - A questionnaire-based cross-sectional study assessing demographics, attitude, spirituality, knowledge and willingness to donate a kidney was conducted among adult Malaysians with oral informed consent. The total number of samples was 1,001 respondents. Univariate and multivariate logistic regression was performed. Findings - A total of 29.17% (n = 292) were willing to donate kidneys, while the remaining 70.83% (n = 709) were not. The mean spirituality score was 80.95 ± 13.79 (maximum score 100), mean attitude score was 52.88 ± 8.074 (maximum score 70) and mean knowledge score was 1.84 ± 0.99 (maximum score 5). A higher score demonstrated a stronger spiritual level, positive attitude and better knowledge. Factors affecting willingness to donate a kidney were ethnicity (odds ratio [OR] = 15.625, 95% confidence interval [CI] = 0.043-0.094) and attitude toward kidney donation score (OR = 0.924, 95% CI = 0.902-0.945). Originality/value - Culture-specific steps to improve programs that may contribute toward improving kidney donation posthumously among Malaysians should be developed. Results drawn from this work demonstrate that policymakers, health-care workers and stakeholders should work together to promote effective policies and program implementation to reduce the ever-increasing gap between the need and shortage crisis of kidney donation.